Da história enquanto crítica: abordagem do pensamento kantiano na tese complementar de Michel Foucault, Gênese e estrutura da antropologia de Kant (1961) - Silva, Tiago Viotto da [UNESP] (2014)
To sets up a bottom line for the study about the idea of history presents in the Michel Foucault’s thought was the goal which guided this dissertation. Therefore, it sought the follow, as a conducting-wire, the read that the French thinker do about Immanuel Kant’s thought, specifically in the text entitled Genesis and structure of Kant’s Anthropology, complementary thesis presented with the major thesis Madness and civilization: a history of insanity in the Age Reason, in 1961. Text which basically aimed to sketch a critique about the contemporaries philosophical anthropologies in the development of the first steps of Foucault’s intellectual labor. Exploring the Foucault’s complementary thesis, it’s possible to establish a hypothesis that these writing allows to define some parameters of an idea of history which, in different ways, will permeate all the path of Foucault’s thought and will culminate in what Foucault later calls Historical Ontology. This dissertation, thus, beyond its own object of study, also fulfills a propaedeutic function, in what that seeks to open up a whole ground/terrain for further investigations about the relationships between Michel Foucault’s work and the history